Flower‐like Cu2In2ZnS5 Nanosheets: A Novel Promising Photoelectrode for Water Splitting. Issue 7 (8th March 2016) - Hong, Tiantian; Liu, Zhifeng; Zhang, Jing; Li, Guangmin; Liu, Junqi; Zhang, Xueqi; Lin, Shaohua
Abstract: This paper describes a promising photoelectrochemical electrode based on a flower‐like Cu2 In2 ZnS5 structure composed of nanosheets and its use as a photoelectrode for photoelectrochemical (PEC) water splitting for the first time. The detailed growth of Cu2 In2 ZnS5 was discussed. The morphology and microstructure were characterized in detail. PEC measurements showed that on the basis of the optimal hydrothermal time, flower‐like Cu2 In2 ZnS5 exhibited high photoelectrochemical activity, as the photocurrent density reached up to 2.00 mA cm −2 . The remarkable PEC performance stems from crucial factors, including improved light absorption, an ideal band gap value, decoupling of the directions of light absorption and charge‐carrier collection, and large surface area. Our results indicate that the flower‐like Cu2 In2 ZnS5 structure composed of nanosheets has enormous potential in PEC water splitting. Abstract : Time to split up : A flower‐like Cu2 In2 ZnS5 structure composed of nanosheets is prepared and used as a photoelectrode for photoelectrochemical water splitting. Cu2 In2 ZnS5 reaches a photocurrent density up to 2.00 mA cm −2 ; this remarkable activity is a result of improved light absorption, an ideal band gap value, decoupling of the directions of light absorption and charge‐carrier collection, and a large surface area.